Magnetic resonance imaging flowmetry demonstrates portal vein dilatation subsequent to oxaliplatin therapy in patients with colorectal liver metastasis. Issue 4 (20th August 2012) - Urdzik, Jozef; Bjerner, Tomas; Wanders, Alkwin; Duraj, Frans; Haglund, Ulf; Norén, Agneta
Abstract Objectives: Sinusoidal injury (SI) after oxaliplatin‐based therapies for colorectal liver metastasis (CRLM) can increase postoperative morbidity. Preoperative methods to estimate SI are lacking. The aim of this study was to identify SI by evaluating portal vein haemodynamics. Methods: Magnetic resonance imaging flowmetry (MRIF) was used to estimate portal vein haemodynamics in 29 patients with CRLM before liver surgery. Sinusoidal injury was evaluated from resected non‐tumorous liver parenchyma according to the combined vascular injury (CVI) score of ≥3. Results: All patients with SI (six of 29) received oxaliplatin; however, a significant association could not be proven (P= 0.148). Oxaliplatin‐treated patients showed portal vein dilatation in both the SI and non‐SI groups compared with patients who had not received oxaliplatin (Bonferroni corrected P= 0.003 and P= 0.039, respectively). Mean portal velocity tended to be lower in patients with SI compared with oxaliplatin‐treated patients without SI (Bonferroni corrected P= 0.087). A mean portal velocity of ≤14.35 cm/s together with a cross‐section area of ≥1.55 cm2 was found to predict SI with sensitivity of 100% and specificity of 78%. Conclusions: Oxaliplatin treatment was associated with portal vein dilatation. Patients with SI showed a tendency towards decreased mean portal flow velocity. This may indicate that SI is associated with an increased resistance to blood flow in the liver parenchyma. Portal vein haemodynamic variables estimated by MRIF can identify patients without SI non‐invasively.